METODE FUZZY ANALYTICAL HIERARCHY PROCESS UNTUK PEMILIHAN NOTEBOOK BERBASIS ANDROID - Akik Hidayat; Ebby Syabilal Rasyad (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2016)
Nowadays, there are many brands of notebook with various specifications and prices are available in markets. This condition makes consumers face difficulties in determining the appropriate option according to their needs and budget. Correspondingly, development of computer has also increased, for instance the use of computer in giving the best decision about a certain issue, in this case it is a matter of choosing a notebook. Therefore, it is important to develop a decision support system in order to choose notebooks by using Fuzzy Analytical Hierarchy Process (FAHP) so that consumers can determine the fittest notebook in accordance with the consumer’s wishes and budget.